Os impactos da primeira adoção das normas IFRS nas demonstrações contábeis das companhias abertas brasileiras - Prado, Thiago Alberto dos Reis (2013)
The overall objective of this research was to identify the change s impact in accounting practices, resulting from the adoption of IFRS on the balance-sheet and income present in the Financial Statements of the Brazilian companies listed on the BM&FBOVESPA. As well as happened in other countries, Brazil adhered to the process of global convergence to IFRS, as issued by instruction nº 457/2007 of the Brazilian Securities Commission (CVM), which determined that IFRS would be mandatory for the consolidated financial statements within financial year 2010 and later. During the convergence process in Brazil, there was concern that the transition rules cause significant differences in items that are the basis for various contracts between economic agents. Through a descriptive study, using the statistical method as a method of procedures and indirect technical documentation, called desk research, that uses secondary data sources, we analyzed the financial statements of 76 nonfinacial companies listed on BM&FBOVESPA, belonging to IBrX Índice Brasil, for the year 2009. To measure the impacts of the transition, we calculated for these companies the inverse of the Gray´s Index of Comparability and identified the items of balance sheet and income statement that showed the largest differences and norms that cause these differences. Results showed significant differences in the groups assets (excluding current liabilities), net income and Debt Composition, with the larger trend metrics in Non-Current Assets, Non-Current Liabilities and Equity, as well as lower net income and a drop in the index Debt Composition. The accounts were the most impacted Fixed Assets, Intangible Assets, Cost of Goods Sold and Revenues. The main rules causing these differences, we highlight the CPC 26 (Minority Interest), CPC 27 (Fixed Assets), CPC 20 (Borrowing Costs) and CPC 38 (Financial Instruments). However, one should note that high standard deviations were found in the impacts of the standards and headings indicating hazards to draw conclusions from individual companies using this data. Furthermore, the results confirm the selected literature that new standards reached each sector differently.